High-sensitivity H i image of diffuse gas and new tidal features in M51 observed by FAST. Issue 2 (9th February 2023) - Yu, Haiyang; Zhu, Ming; Xu, Jin-Long; Ai, Mei; Jiang, Peng; Yang, Yanbin
ABSTRACT: We observed the classical interacting galaxy M51 with FAST and obtain high-sensitivity H i image with column density down to 3.8 × 10 18 cm −2 . In the image we can see a diffuse extended envelope around the system and several new tidal features. We also get a deeper look at M51b's probable gas, which has an approximated velocity range of 560 to 740 km s −1 and a flux of 7.5 Jy km s −1 . Compared to the VLA image, we observe more complete structures of the Southeast Tail, Northeast Cloud, and Northwest Plume, as well as new features of the Northwest Cloud and Southwest Plume. M51's most prominent tidal feature, the Southeast Tail, looks very long and broad, in addition to the two small detached clouds at the periphery. Due to the presence of optical and simulated counterparts, the Northwest Cloud appears to be the tail of M51a, while the Northwest Plume is more likely a tidal tail of M51b. The large mass of the Northwest Plume suggests that M51b may have been as gas-rich as M51a before the interaction. In addition, the formation process of the Northeast Cloud and Southwest Plume is obscured by the lack of optical and simulated counterparts. These novel tidal features, together with M51b's probable gas, will inspire future simulations and provide a deeper understanding of the evolution of this interacting system.